(untitled) (Research, Society and Development, 2021)
Introduction: Osteonecrosis of the jaws associated with the use of medications is a disease that occurs through the use of therapies with antiresorptive drugs, such as bisphosphonates and Denosumab, or antiangiogenics. Although the manifestation of this disease does not have a high incidence, its occurrence generates a significant impact on the patient’s life, leading to painful symptoms, with suppuration and a foul odor. Despite the various treatments used, there is no consensus on the greater effectiveness of one treatment compared to another. Thus, this work aims to demonstrate the different treatment modalities and the benefits allied to each one. Materials and Methods: Searches made in the PubMed / MEDLINE database on the theme Osteonecrosis of the Jaws Associated with the Use of Medicines, together with Boolean operators, during May, June and July 2020. Results: The search resulted in 143 articles and, after applying the eligibility criteria, 49 were selected (23 prospective studies, 17 retrospective and 9 case series), comprising 2617 patients and 2848 injuries. The treatments were divided into 5 modalities (adjuvant therapies, aggressive surgical treatments, tissue therapies, medication-assisted treatment and conservative surgical therapies). Conclusion: Several treatments are proposed and it seems clear that aggressive surgeries are the therapies with the best results, especially when combined with tissue or adjuvant therapy. Conservative surgeries play an important role, especially in patients with systemic conditions that contraindicate major surgeries.